2016
DOI: 10.1155/2016/4108490
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab Injection as an Adjuvant in the Treatment of Neovascular Glaucoma Accompanied by Vitreous Hemorrhage after Diabetic Vitrectomy

Abstract: Purpose. To determine the efficacy of intravitreal ranibizumab injection as adjuvant therapy in the treatment of neovascular glaucoma (NVG) accompanied by postvitrectomy diabetic vitreous hemorrhage (PDVH). Methods. Eighteen NVG patients (18 eyes) accompanied by PDVH were enrolled in this prospective, monocenter, 12-month, interventional case series. The consecutive 18 patients with an IOP ≥ 25 mmHg despite being treated with the maximum medical therapy were treated with intravitreal ranibizumab injections. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…[ 2 , 54 , 57 ] In addition, after using anti-VEGF agents as an adjuvant therapy with glaucoma surgery, the results have been better than previous treatments. [ 58 60 ] There have even been studies reporting NVG regression after treatment with anti-VEGF agents, with or without PRP. [ 61 63 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 54 , 57 ] In addition, after using anti-VEGF agents as an adjuvant therapy with glaucoma surgery, the results have been better than previous treatments. [ 58 60 ] There have even been studies reporting NVG regression after treatment with anti-VEGF agents, with or without PRP. [ 61 63 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous data reporting practical experience with anti-VEGF agents, as well as general considerations about the disease, suggest that an early endpoint is appropriate to detect whether the treatment with anti-VEGF is able to provide earlier control of the disease manifestations than standard treatment options. The evaluation timing for the primary endpoint was therefore determined to be at week 1 [7][8][9]. Limitations of this study include that, for ethical reasons, treatment with systemic IOPlowering treatments was permitted throughout the study, because elevated IOP can quickly lead to irreversible loss of vision [2].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal ischemia, thought to be the mediator in the majority of NVG cases [4], results in the release of angiogenic factors, such as vascular endothelial growth factor (VEGF), which trigger neovascularization [2]. It has been suggested that anti-VEGF treatments have a positive influence on outcomes in patients with NVG [7][8][9]. The results of the VEGA and VENERA studies supported the approval of intravitreal aflibercept (IVT-AFL) injection (2 mg) in 2020 as a treatment for patients with NVG in Japan [10].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown contradictory results regarding the intravitreal use of anti-VEGF drugs with the goal of preventing NVG. A number of researchers believe that intravitreal use of anti-VEGF may improve clinical manifestation of NVG and that treatment with these drugs could be very useful [ 21 ]. There have been published controversial studies in which other researchers disagree with the aforementioned view, believing that the anti-VEGF application itself, and especially its longer use, can lead to an increase in IOP, thus increasing the risk of glaucoma occurrence and progression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%